Answer:
4x -12
Step-by-step explanation:
Your question answers itself: you use the distributive property to remove the parentheses.
4(x -3) = 4(x) +4(-3) = 4x -12
Answer:try sin 14/x
Step-by-step explanation:
Answer:
because they have little anty bodies.
Step-by-step explanation:
i don't know
G(x) = f(x) +5
= 4^x -6 +5
= 4^x -1
The 3rd selection is appropriate.
Student B is wrong , student A is correct in simplifying the expression .
Expression B must be simplified to cot θ .
Formulas to be used are :
1 -
θ =
θ
1 -
θ =
θ .
Since , location of error is step 3 , we will start from there
[ ( 1 -
θ ) / sin θ ] / cos θ = [ ( 1 -
θ ) / sin θ ] * [ 1 / cos θ ]
= ( 1 -
θ ) / ( sin θ * cos θ )
=
θ / ( sin θ * cos θ )
= cot θ .
To know more on trigonometry follow link :
brainly.com/question/24349828
#SPJ4
Since , the question is incomplete we assume it to be :